Socio-Economic Factors and Project Implementation in Government Aided Secondary Schools in Kabale Distric - Turyasingura, John Bosco; Moses, Agaba (American Journal of Humanities and Social Sciences Research, 2022)
This study was set to establish the effect of social-economic factors on project implementation in Government aided secondary schools in Uganda a case study of Kabale District. The elements of social economic factors were: good Leadership, Team motivation and Planning. This study adopted This study used a cross-sectional survey research design adopting quantitative and qualitative approaches. The quantitative approach helps to describe the current conditions and to investigate cause and effect relationships between the study variables. Data was collected in the means of administering a questionnaire survey from a sample of 162respondents. SSP was used to test hypotheses. Findings revealed that, (r = ..962, P≤.01). The study recommends that the social-economic factors such asgood Leadership, Team motivation and Planning should be put into consideration when the government is providing/ giving resources to facilitate projects in Government Aided secondary schools in Kabale District